Decision management systems : a practical guide to using business rules and predictive analytics - Taylor, James (Upper Saddle River, NJ : IBM Press/Pearson plc, 2012)
Shows how to integrate operational and analytic technologies to create systems that are more agile, more analytic, and more adaptive.
Includes bibliographical references (p. 267-270) and index.
oif 16/06/15
Loan
Keywords: Decision support systems; Decision making